Design and experimental study on full-metal sealing structure of mandrel-type casing hanger. (May 2019) - Liu, Yang; Lian, Zhanghua; Deng, Changsong; Zhang, Qiang; Mu, Yisheng
To avoid the failure of mandrel-type casing hanger, this article provides a new type of metal sealing structure, and the sealing is achieved through plastic flow of soft metal and elastic deformation of matrix. A finite element analysis model for sealing performance of mandrel-type hanger is established to study the deformation and contact pressure of sealing cone. Among the four sealing structures studied in this article, the elliptic surface is the optimal. It is suggested to design smaller equal cone angle of inner cone angle ( β ) and outer cone angle ( α ) in the limited space as far as possible so as to obtain larger average contact pressure. These findings can provide references for the structural design of the seal area of the mandrel-type hanger. The sealing test results show that the sealing curve turns to be a straight line under water pressure and air pressure of 140 MPa. The results of theoretical study and laboratory experiment show that the sealing structure of full-metal multilevel conical elliptical surface is reliable and can meet the sealing requirements of the oil field wellhead device under limit working condition of 140 MPa.